Evolutionary game analysis of three parties in logistics platforms and freight transportation companies’ behavioral strategies for horizontal collaboration considering vehicle capacity utilization - Shuai Deng; Duohong Zhou; Guohua Wu; Ling Wang; Ge You (Complex & Intelligent Systems, 2022)
Abstract In China, logistics platforms are an effective way to solve vehicle capacity utilization using information sharing. However, most logistics platforms do not possess operational sustainability due to excessive profit-seeking. To address this problem, conflicts of interest among freight transportation participants are discussed using a stakeholder approach. A three-player evolutionary game model (TEGM) is developed to analyze the interactions among freight carriers, freight shippers, and logistics platforms. Then, the asymptotic equilibrium and evolutionary stability strategies of the three-player game are analyzed. The results indicate that a high-level positive network externality is the driving force behind the logistics platform’s “high-level service”. A fairness payment incentive guarantees a “sharing” strategy for freight carriers and shippers. When the high-level positive network externality is limited and lower than a threshold value, there is no stable equilibrium point in the TEGM. A government tax incentive cannot change the freight carriers’ and shippers’ strategy to participate in this horizontal collaboration system, except for the logistics platform’s probability of providing “high-level service”. However, the behavioral strategies of the freight transportation participants can be changed to achieve the sustainability of freight transportation by reducing the value-added tax rate through the logistics platform and increasing the high-level positive network externality of the logistics platform and other participants’ perceived fairness through a payment incentive. Finally, suggestions for regulating the behaviors of freight transportation participants and promoting the sustainability of freight transportation are discussed.